El clima organizacional y el desempeño laboral en el contexto del personal administrativo de la Universidad Técnica de Cotopaxi - Albán Raura, María Belén (2023)
The organizational climate in the human talent that works in the administrative area of the UTC, has taken on enormous relevance, considering that it is in this place where they spend most of their time; Therefore, the objective of the research was to analyze the organizational climate in the context of the administrative staff of the Technical University of Cotopaxi and its effect on work performance, for which an analysis of 5 dimensions was carried out, such as: communication, physical conditions , collaboration, leadership, organization and responsibility, the same ones that constitute fundamental axes for an institution that provides educational services.